Toxicology Evaluation of Drugs Administered via Uncommon Routes: Intranasal, Intraocular, Intrathecal/Intraspinal, and Intra-Articular. (January 2018) - Emami, Armaghan; Tepper, Jeff; Short, Brian; Yaksh, Tony L.; Bendele, Alison M.; Ramani, Thulasi; Cisternas, Alvaro F.; Chang, Jay H.; Mellon, R. Daniel
As the need for nasal, ocular, spinal, and articular therapeutic compounds increases, toxicology assessments of drugs administered via these routes play an important role in human safety. This symposium outlined the local and systemic evaluation to support safety during the development of these drugs in nonclinical models with some case studies. Discussions included selection of appropriate species for the intended route; conducting nonclinical studies that closely mimic the intended use with adequate duration; functional assessment, if deemed necessary; evaluation of local tissues with special histological staining procedure; and evaluations of safety margins based on local and systemic toxicity.